1998
DOI: 10.1590/s0036-46651998000600001
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviruses Isolated From Patients With Acute Respiratory Infections During Seven Years in Rio De Janeiro (1985-1991)

Abstract: Enteroviruses were investigated in respiratory secretions collected from patients with acute respiratory infections (ARI) over a seven year period (1985-1991), as part of a longitudinal study of ARI aetiology. All the viruses that are most commonly associated with ARI were found in this study. Among the virus isolates, enteroviruses were only less frequent than respiratory syncytial viruses, adenoviruses and influenzaviruses. Forty five enterovirus samples were isolated from patients with either upper respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
2
11
0
4
Order By: Relevance
“…Significant differences in age distribution were seen in influenza and RSV (p,0.001), also in seven other pathogens EV, ADV, PIV2, PIV3, HBoV, HMPV and MP (p#0.009) ( Table 2), and different age groups showed different distribution peaks ( Figure 2). This was consistent with previous serologic and epidemiologic studies of these pathogens [20,22,31,33,40,[55][56][57]. For the seven remaining pathogens no statistical differences in age distribution or few positive samples were found to analyze.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Significant differences in age distribution were seen in influenza and RSV (p,0.001), also in seven other pathogens EV, ADV, PIV2, PIV3, HBoV, HMPV and MP (p#0.009) ( Table 2), and different age groups showed different distribution peaks ( Figure 2). This was consistent with previous serologic and epidemiologic studies of these pathogens [20,22,31,33,40,[55][56][57]. For the seven remaining pathogens no statistical differences in age distribution or few positive samples were found to analyze.…”
Section: Discussionsupporting
confidence: 91%
“…EV is frequently isolated from the throats of people with respiratory infection and many studies have supported the role of EV in ARI [29][30]. In a seven-year study in Rio de Janeiro EV was found less frequently than RSV, ADV and influenza viruses in patients with ARI [31].…”
Section: Discussionmentioning
confidence: 99%
“…16 Till date, it is unclear which are the dominant serotypes or groups in airway infections. 16,17,21,22 CB3, CB5, and Echo20 were addressed to be related to the so-called "summer grippe" or common cold. 23 CA2, CA4e6, CA10, CB1, CB2, and CB5, and Echo9, Echo18, and Echo30 had also been isolated or identified from children with acute tonsillitis in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus, RSV, and parainfluenza viruses can cause severe disease particularly in children, accounting for a considerable proportion of childhood morbidity and mortality [1], [2]. Enteroviruses and HSV have been isolated from patients with acute respiratory infections and these viruses may also cause infections such as pharyngitis [3], [4]. Patients infected by these diverse viral pathogens present with widely overlapping symptomology, which render clinical diagnosis unreliable and severely limits etio-epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%